Pengaruh Pembelajaran Konstruktivistik terhadap Hasil Belajar Siswa pada Mata Pelajaran IPAS Kelas V SD - Khaeriyah, Ainun; Rosmalah, Rosmalah; Satriani, DH, Satriani, DH (Universtas Negeri Makassar, 2025)
This study is a quantitative study with a one group pretest-posttest design that aims to: (1) describe the learning outcomes of fifth grade students of SD Negeri 190 Launga before and after the implementation of constructivist learning, and (2) analyze the significant effect of the implementation of constructivist learning on science learning outcomes. The subjects of the study were 19 students. Data were collected through pretest and posttest, then analyzed using SPSS version 26 through normality, homogeneity, and Paired Sample t-Test tests. The results showed a significant increase: the average pretest score of 45.96 increased to 76.14 in the posttest. Before the treatment, most students were in the less and very less categories, while after the implementation of constructivist learning the majority of students were in the good and very good categories. The Paired Sample t-Test test showed a significance value of 0.000 (<0.05) and tcount 15.107> ttable 2.10092, which indicated a significant effect. Thus, the application of constructivist learning has proven effective in improving student learning outcomes in science subjects.